Effect of supplementing total mixed ration with ajwain (Trachyspermum ammi) oil on the performance of buffalo calves - WADHWA, M; BAKSHI, M P S (The Indian Journal of Animal Sciences, 2019)
This study was taken up to assess the impact of different levels of ajwain oil (rich in essential oils) on the nutrient utilization by in vitro gas production technique. The best level of ajwain oil obtained was tested on the performance of buffalo calves. Ajwain oil was supplemented at 0.05, 0.1, 0.15 and 0.2% of total mixed ration (TMR; concentrate:green fodder:wheat straw in 40:48:12 ratio on DM basis). The results revealed that supplementation of incremental levels of ajwain oil to the TMR resulted in linear decrease in net gas production (NGP), digestibility of true OM and NDF; ME availability and methane production. Supplementing the TMR with ajwain oil beyond 0.05% resulted in significant depression in total and individual volatile fatty acids (VFAs) and acetate to propionate ratio. The protozoa numbers declined linearly with increase in level of ajwain oil supplementation. Hence 0.05% level of ajwain oil was selected for assessing its impact on performance of growing buffalo calves. In the first experiment, a 146-day feeding trial was conducted on 20 male buffalo calves divided into 2 groups, offered a TMR-1 (concentrate: green fodder: wheat straw ratio of 40:48:12 on DM basis) or TMR-1 supplemented with 0.05% ajwain oil. After completion of this trial, another 138-day feeding trial was conducted on 18 male buffalo calves divided into 2 groups and were offered a TMR-2 (concentrate: wheat straw ratio of 50:50 on DM basis) or TMR-2 supplemented with 0.05% ajwain oil. In the first growth trial, supplementing the control diet with ajwain oil did not show any impact on daily DM intake, digestibility of nutrients and N-retention, but in the second experiment the digestibility of all the nutrients, except that of crude protein was improved significantly in the ajwain oil supplemented group. The daily DM intake and N-retention was comparable in both the groups. The blood profile, urinary purine derivatives excretion and microbial biomass synthesis was not affected by ajwain oil supplementation during both the experiments. The average daily gain was comparable between control and ajwain oil supplemented group in both the feeding trials. It was concluded that supplementing ajwain oil to the TMR suppressed the in vitro methane production; improved the digestibility of nutrients in wheat straw based TMR supplemented with 0.05% ajwain oil, but did not show any significant beneficial effect on the performance of buffalo calves.